2019
DOI: 10.1088/1742-6596/1359/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the liquid fuel spraying based on Eulerian-Lagrangian model

Abstract: The paper presents test results of the method for numerical simulation of liquid fuel spraying based on the Eulerian-Lagrangian model. This model describes the fluid flow inside the injector and directly behind it using the Euler-VOF method, while the dispersed medium (droplets) formed at a certain distance from the injector is described using the Lagrange approach. When using the VOF (volume of fluid method), the dynamical adjustment of the calculation grid at the phase interface is applied. Turbulence is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is shown that for complex flows the RSM, along with large eddy simulation methods, allows sufficiently correct solutions. We also tested the methodology for modeling atomization of a gas-liquid flow based on the VOF (Volume of fluid) method [5], ELSA (Eulerian-Lagrangian Spray Atomization, VOF to DPM) [6] and Lagrange [7]. The calculation results have shown acceptable agreement with the experiment by the main characteristics of atomization and allowed qualitatively correct determination of the two-phase flow structure, parameters and shapes of droplets, and the velocity and direction of their movement.…”
Section: Problem Statement and Research Methodsmentioning
confidence: 99%
“…It is shown that for complex flows the RSM, along with large eddy simulation methods, allows sufficiently correct solutions. We also tested the methodology for modeling atomization of a gas-liquid flow based on the VOF (Volume of fluid) method [5], ELSA (Eulerian-Lagrangian Spray Atomization, VOF to DPM) [6] and Lagrange [7]. The calculation results have shown acceptable agreement with the experiment by the main characteristics of atomization and allowed qualitatively correct determination of the two-phase flow structure, parameters and shapes of droplets, and the velocity and direction of their movement.…”
Section: Problem Statement and Research Methodsmentioning
confidence: 99%